The Role Of African Culture In Shaping Modern Healthcare Practices In Nigeria - Oyewale Oluwaseun, (PEOPLE: International Journal of Social Sciences, 2025)
African heritage profoundly impacted the development of modern healthcare in Nigeria through the integration of its traditional beliefs and contemporary culture. Traditional healthcare systems are engraved in cultural elements such as herbal medicine, spiritual healing, and the worship of deities like Osanyin (the god of herbal medicine) and Babalawo (traditional healers) among the Yorubas. In the Igbo culture of southeastern Nigeria, traditional medicine involves the use of herbs, rituals, and the role of dibias (healers) who diagnose and treat illnesses through spiritual and natural means. Similarly, the Hausa people of northern Nigeria rely on traditional healing methods, including the use of magani (herbal remedies) and Islamic medicine. These practices are found across Yorubaland, Igboland and Hausaland have historically emphasized holistic healing, balancing physical, spiritual, and emotional well-being. This research investigates the impact of culturally specific practices like herbalists, spiritualists, and other forms of primary healthcare, on the evolution of healthcare systems in Nigeria. This study will use a mixed-methods approach, combining qualitative analysis of secondary data including scholarly books, peer-reviewed articles, historical records, and ethnographic data with interviews of traditional healers and healthcare professionals to examine how these cultural practices have been integrated into modern healthcare systems. The study highlights public health concern by emphasising the need to integrate both traditional and contemporary methods of medicine. It was revealed that Nigerian healthcare systems operate efficiently with the integration of traditional and contemporay medicine that is practised in a culturally respectful manner. This not only improves the acceptance of healthcare services, but also builds confidence among complex societies. This research indicates that the understanding and integration of African anthropology into healthcare policy formulation will improve the efficacy and sustainability of healthcare delivery systems in Nigeria.